Direct transfer of micro-molded electrodes for enhanced mass transport and water management in PEMFC - Deshmukh, Ashvini B.; Kale, Vinayak S.; Dhavale, Vishal M.; Sreekumar, K.; Vijayamohanan, K.; Shelke, Manjusha V. (Electrochemistry Communications, 2010)
Soft lithography technique is used to micropattern the electrodes on the electrolyte membrane of polymer electrolyte fuel cell (PEMFC) in order to alleviate the issues due to poor water management and inadequate reactant distribution in the fuel cell environment. Membrane electrode assembly with the micropatterned electrode has shown an increase in power density at a higher temperature as well as at a higher relative humidity when compared to a flat electrode. Consistency in cell performance is observed in the case of micropatterned electrodes. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Bipolar plate-less PEM fuel cell; Micropatterned electrodes; Microtransfer molding; Soft lithography

High aspect ratio nanoscale multifunctional materials derived from hollow carbon nanofiber by polymer insertion and metal decoration - Balan, Beena K.; Kale, Vinayak S.; Aher, Pradnya P.; Shelke, Manjusha V.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2010)
A novel high aspect ratio material which can simultaneously display multiple functions such as proton and electron conductivity and electrocatalytic activity has been developed by incorporating both platinum nanoparticles and phosphoric acid doped polybenzimidazole along the inner and outer surfaces of a hollow carbon nanofiber.

Template assisted highly ordered novel self assembly of micro-reservoirs and its replication - Hire, Santosh L.; Shelke, Manjusha V.; Kale, Vinayak S.; Galopin, Elisabeth; Kulkarni, Mohan G.; Boukherroub, Rabah; Ogale, Satishchandra B. (Lab on a Chip, 2010)
A novel method is developed for template assisted fabrication of a regular assembly of microcavity arrays. Simple micropatterns on PDMS mold are used to create complex geometries via solvent vapor back pressure in a biodegradable polymer. Cavities are in turn replicated in complimentary PDMS mushroom like microstructures.

Novel catalyst-free synthesis of vertically aligned silicon nanowire-carbon nanotube heterojunction arrays for high performance electron field emitters - Kale, Vinayak S.; Sathe, Bhaskar R.; Kushwaha, Ajay; Aslam, Mohammed; Shelke, Manjusha V. (Chemical Communications, 2011)
A novel, catalyst-free strategy for the direct synthesis of vertically aligned silicon nanowire-carbon nanotube (SiNW-CNT) heterojunction arrays is presented. Such a heterojunction with the junction area in the nanoscale displays enhanced field emission characteristics at low turn-on field, with a nearly three times increase in the field enhancement factor.

Synthesis of silver nanoparticles in an aqueous suspension of graphene oxide sheets and its antimicrobial activity - Das, Manash R.; Sarma, Rupak K.; Saikia, Ratul; Kale, Vinayak S.; Shelke, Manjusha V.; Sengupta, Pinaki (Colloids and Surfaces B-Biointerfaces, 2011)
A solution-based approach to the synthesis of silver (Ag) nanoparticles by chemical reduction of AgNO3 in a graphene oxide (GrO) suspension is demonstrated. X-ray diffraction and transmission electron microscopy indicate that the Ag nanoparticles, of size range 5-25 nm, were decorated on the GrO sheets. The size and shape of the Ag nanoparticles are dependent on the concentration of the AgNO3 solution. Antimicrobial activity of such hybrids materials is investigated against the Gram negative bacteria Escherichia coli and Pseudomonous aeruginosa. The bacterial growth kinetics was monitored in nutrient broth supplemented with the Ag nanoparticle-GrO suspension at different conditions. It was observed that P. aeruginosa is comparatively more sensitive to the Ag nanoparticle-GrO suspension. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial activity; Escherichia coli; graphene oxide; Pseudomonous aeruginosa; Silver nanoparticle

High efficiency electron field emission from protruded graphene oxide nanosheets supported on sharp silicon nanowires - Devarapalli, Rami Reddy; Kashid, Ranjit V.; Deshmukh, Ashvini B.; Sharma, Ponchami; Das, Manash R.; More, Mahendra A.; Shelke, Manjusha V. (Journal of Materials Chemistry C, 2013)
Graphene oxide (GO) potentially has applications in vacuum microelectronic devices for realization of field emission displays. Graphene and its derivatives are expected to be efficient field emitters due to their unique electrical properties. However, the flat sheet structure of graphene or GO allows electron field emission only from the edges of graphene and GO nanosheets. In order to extract maximum field emission current density at lower applied voltage from the GO nanosheets, we supported and stretched them on sharp tips of silicon nanowires (SiNWs). Highly efficient and stable field emission with low turn-on field was observed for these SiNW-GO heterostructures. The sharp protrusions created by stretching of the GO nanosheets on SiNWs locally enhance the electric field and thus enhance the field emission characteristics. The dominant use of silicon in electronic devices makes this approach robust for the development of field emission devices using graphene based field emitters.

One-pot synthesis of gold nanoparticle/molybdenum cluster/graphene oxide nanocomposite and its photocatalytic activity - Barras, Alexandre; Das, Manash R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Cordier, Stephane; Szunerits, Sabine; Boukherroub, Rabah (Applied Catalysis B-Environmental, 2013)
The paper reports on a facile one-pot synthesis of a tri-component gold nanoparticle/molybdenum cluster/graphene oxide (AuNPs@Mo-GO) nanohybrid composite. The synthetic methodology consists on direct UV irradiation of an aqueous solution containing graphene oxide (GO), Na-2[Mo6Br8(N-3)(6)], HAuCl4 center dot 3H(2)O and isopropanol at room temperature in air using a UV fiber lamp. The composite material exhibits very high photocatalytic activity for the degradation of rhodamine B under visible light irradation. The resulting nanohybrid material was characterized using Raman spectroscopy, UV-vis spectrometry, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). (c) 2012 Elsevier B.V. All rights reserved.
Keywords: gold nanoparticles; graphene oxide; Nanohybrid; Photodegradation; Rhodamine B; visible light; [Mo6Br8(N-3)(6)](2-)cluster

Synthesis and electrochemical performance of a single walled carbon nanohorn-Fe3O4 nanocomposite supercapacitor electrode - Deshmukh, Ashvini B.; Shelke, Manjusha V. (RSC Advances, 2013)
A new Fe3O4-SWCNH nanocomposite was synthesized as an electrode material for supercapacitors. The nanocomposite exhibited a high specific capacitance of 377 F g(-1) and delivered a stable discharge capacitance at a current density of 1 A g(-1) over 1000 cycles between 0 and 1.2 V.

C@SiNW/TiO2 core-shell nanoarrays with sandwiched carbon passivation layer as high efficiency photoelectrode for water splitting - Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Shelke, Manjusha V. (Scientific Reports, 2014)
One-dimensional heterostructure nanoarrays are efficiently promising as high performance electrodes for photo electrochemical (PEC) water splitting applications, wherein it is highly desirable for the electrode to have a broad light absorption, efficient charge separation and redox properties as well as defect free surface with high area suitable for fast interfacial charge transfer. We present highly active and unique photoelectrode for solar H-2 production, consisting of silicon nanowires (SiNWs)/TiO2 core-shell structures. SiNWs are passivated to reduce defect sites and protected against oxidation in air or water by forming very thin carbon layer sandwiched between SiNW and TiO2 surfaces. This carbon layer decreases recombination rates and also enhances the interfacial charge transfer between the silicon and TiO2. A systematic investigation of the role of SiNW length and TiO2 thickness on photocurrent reveals enhanced photocurrent density up to 5.97 mA/cm(2) at 1.0 V vs. NHE by using C@SiNW/TiO2 nanoarrays with photo electrochemical efficiency of 1.17%.

Electrochemical preparation of vertically aligned, hollow CdSe nanotubes and their p-n junction hybrids with electrodeposited Cu2O - Debgupta, Joyashish; Devarapalli, Rami Reddy; Rahman, Shakeelur; Shelke, Manjusha V.; Pillai, Vijayamohanan K. (Nanoscale, 2014)
Vertically aligned, hollow nanotubes of CdSe are grown on fluorine doped tin oxide (FTO) coated glass substrates by ZnO nanowire template-assisted electrodeposition technique, followed by selective removal of the ZnO core using NH4OH. A detailed mechanism of nucleation and anisotropic growth kinetics of nanotubes have been studied by a combination of characterization tools such as chronoamperometry, SEM and TEM. Interestingly, ``as grown'' CdSe nanotubes (CdSe NTs) on FTO coated glass plates behave as n-type semiconductors exhibiting an excellent photo-response (with a generated photocurrent density value of similar to 470 mu A cm(-2)) white in contact with p-type Cu2O (p-type semiconductor, grown separately on FTO plates) because of the formation of a n-p heterojunction (type II). The observed photoresponse is 3 times higher than that of a similar device prepared with electrodeposited CdSe films (not nanotubes) and Cu2P on FTO. This has been attributed to the hollow 1-D nature of CdSe NTs, which provides enhanced inner and outer surface areas for better absorption of light and also assists faster transport of photogenerated charge carriers.

Enhanced photoluminescence and photoactivity of plasmon sensitized nSiNWs/TiO2 heterostructures - Yenchalwar, Sandeep G.; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V. (Physical Chemistry Chemical Physics, 2014)
A light sensitive wide band gap radial heterojunction between TiO2 and nSiNWs sensitized by gold nanoparticles is reported. The surface plasmon of AuNPs influences the optical and photocurrent properties of the heterojunction considerably. Improvement in the band gap emission of TiO2 has been found at the expense of defect radiation. Excitation of AuNPs deposited on nSiNWs/TiO2 by light irradiation shows a wavelength-dependent photocurrent due to the increased photoactivity of the heterojunction.

Evaluation of n-type ternary metal oxide NiMn2O4 nanomaterial for humidity sensing - Gawli, Yogesh; Badadhe, Satish S.; Basu, Aniruddha; Guin, Debanjan; Shelke, Manjusha V.; Ogale, Satishchandra (Sensors and Actuators B-Chemical, 2014)
Synthesis of mono-dispersed oleic acid (OA) capped NiMn2O4 (NMO) nanoparticles and their use for humidity sensing is reported. Oleic acid capped NMO (NMO-cOA) nanoparticles are synthesized from nickel oleate and manganese oleate complex. NiMn2O4 is obtained by removing oleic acid capping at 500 degrees C in air. X-ray diffraction analysis shows formation of pure NiMn2O4 phase which is also confirmed by HRTEM-SAED analysis. The TEM analysis also shows that the nanoparticles are nearly mono-dispersed. Doctor bladed films of NMO nanoparticles are seen to exhibit excellent humidity sensing property. The resistivity is seen to change by two orders with humidity change from 11% RH to 92% RH with fairly good linearity over the entire range. The response and recovery times are also fast. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Humidity; Impedance; Nanoparticles; NiMn2O4; Oleic acid; Sensor

Functional silicon nanostructures derived from drying-mediated self-assembly of gold nanoparticles - Deshmukh, Ashvini B.; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Journal of Nanoparticle Research, 2014)
Self-assembly of nanoparticles is an efficient technique where nanobuilding blocks spontaneously organize into ordered structures by thermodynamic and other constraints. We demonstrate that multifunctional Silicon (Si) nanostructures with unique morphologies like sheets, plates and flakes can be etched chemically by taking an advantage of natural self-assembly of gold nanoparticles (AuNPs) characterized with drying kinetics under external stimuli. We further demonstrated antireflection properties of the as-synthesized Si nanostructures.
Keywords: Antireflective material; gold nanoparticles; Metal-assisted chemical etching; Self-assembly; Si Nanostructures

Nanodiamond particles/reduced graphene oxide composites as efficient supercapacitor electrodes - Wang, Qi; Plylahan, Nareerat; Shelke, Manjusha V.; Devarapalli, Rami Reddy; Li, Musen; Subramanian, Palaniappan; Djenizian, Thierry; Boukherroub, Rabah; Szunerits, Sabine (Carbon, 2014)
The paper reports on the preparation of reduced graphene oxide (rGO) modified with nanodiamond particles composites by a simple solution phase and their use as efficient electrode in electrochemical supercapacitors. The technique relies on heating aqueous solutions of graphene oxide (GO) and nanodiamond particles (NDs) at different ratios at 100 degrees C for 48 h. The morphological properties, chemical composition and electrochemical behavior of the resulting rGO/NDs nanocomposites were investigated using UV/vis spectrometry, Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, transmission electron microscopy (TEM) and electrochemical means. The electrochemical performance, including the capacitive behavior of the rGO/NDs composites were investigated by cyclic voltammetry and galvanostatic charge/discharge curves at 1 and 2 A g(-1) in 1 M H2SO4. The rGO/ND matrix with 10/1 ratio displayed the best performance with a specific capacitance of 186 +/- 10 F g (-1) and excellent cycling stability. (C) 2013 Elsevier Ltd. All rights reserved.

Plasmon-enhanced photocurrent generation from click-chemically modified graphene - Yenchalwar, Sandeep G.; Devarapalli, Rami Reddy; Deshmukh, Ashvini B.; Shelke, Manjusha V. (Chemistry-A European Journal, 2014)
The visible-light response of Au nanoparticles (AuNPs) assembled on rGO through different molecular bridges was investigated by transient photocurrent generation. We prepared rGO with two self-assembled monolayers (SAMs), one linear and the other with aromatic triazoles through a click cycloaddition reaction. A fivefold photocurrent enhancement was observed for triazole linkers over the aminopropyltrimethoxysilane (APTMS) linker. Cyclic voltammetry (CV) and impedance measurements also suggest fast electron transfer on account of the low resistance offered by the click-modified rGO surface whereby introduction of triazoles offers the efficient bridge between the donor AuNPs and acceptor rGO.
Keywords: Gold; graphene; Nanoparticles; photophysics; surface plasmon resonance

Quantum dot-decorated silicon nanowires as efficient photoelectrodes for photoelectrochemical hydrogen generation - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)
Quantum dot-decorated wide band gap semiconductors, such as TiO2, ZnO, SnO2, etc., which have electron mobilities of less than 200 cm(2) V-1 S-1 have been well studied as the photoelectrodes for photovoltaics and photoelectrochemical water splitting. Herein, we report CdSe quantum dot decorated-silicon nanowires (SiNWs) as photoelectrodes for photoelectrochemical water splitting. SiNWs have a comparatively higher electron mobility than metal oxides. A photocurrent density of around 6.1 mA cm(-2) was obtained for the CdSe/SiNWs photoelectrode, which is nearly five times higher than that for SiNWs alone and which also shows a good transient photocurrent response. The band energy level alignment was also studied between Si and CdSe by observing the corresponding flat band potentials from a Mott-Schottky analysis.

Synthesis and electrochemical performance of a single walled carbon nanohorn-Fe3O4 nanocomposite supercapacitor electrode (vol 3, pg 21390, 2013) - Deshmukh, Ashvini B.; Shelke, Manjusha V. (RSC Advances, 2014)

Synthesis and electrochemistry of pseudocapacitive multilayer fullerenes and MnO2 nanocomposites - Azhagan, Muniraj Vedi Kuyil; Vaishampayan, Mukta V.; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)
Electrode materials with efficient capabilities for ionic and electronic transport are key to high performance supercapacitors. Here, we demonstrate a simple and comparatively low temperature synthesis of functionalized multilayer fullerenes so called carbon nano-onions (CNOs) as the electrode for high performance electrochemical supercapacitors. The exohedral type supercapacitor formed due to nonporous CNOs showed higher specific capacitance than conventional graphitic/mesoporous/activated carbons. Surface redox functionalities of these CNOs add up to significant pseudocapacitance. Further in situ incorporation of MnO2 nanoparticles to these CNOs increased the specific capacitance up to 1207 F g(-1), which is close to the theoretical value of pseudocapacitive MnO2.

Synthesis and electrochemistry of pseudocapacitive multilayer fullerenes and MnO2 nanocomposites (vol 2, pg 2152, 2014) - Azhagan, Muniraj Vedi Kuyil; Vaishampayan, Mukta V.; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)

Green approach for the decoration of Pd nanoparticles on graphene nanosheets: an in situ process for the reduction of C-C double bonds and a reusable catalyst for the suzuki cross-coupling reaction - Hussain, Najrul; Borah, Ashwini; Darabdhara, Gitashree; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (New Journal of Chemistry, 2015)
A new strategy for in situ synthesis of palladium nanoparticles (Pd NPs) decorated on reduced graphene oxide (rGO) nanosheets with controlled size and shape is reported. This strategy was designed as three processes in one pot, namely, (a) reduction of graphene oxide, (b) formation of Pd NPs on the rGO nanosheets and (c) simultaneous reduction of olefin. In this synthesis process, a hydrogen atmosphere was used to develop the Pd NPs-rGO nanocatalyst, which is reusable and easily separable. The influence of the size and morphology of the Pd-rGO-H-2 catalyst on the catalytic activity in the Suzuki cross-coupling reaction was investigated by comparing with other catalysts, Pd-rGO-As and Pd-rGO-Gl, and they were synthesized by different reducing agents, ascorbic acid and glucose, respectively. The catalysts were characterized by electron microscopy (HRTEM, SEM), FT-IR, XRD and XPS. The Pd-rGO-H-2 catalyst was found to possess excellent catalytic activity and recyclability in the Suzuki cross-coupling reaction under mild reaction conditions.

Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2015)
Highly stable Cu(0) nanoparticles were synthesized on reduced graphene oxide (rGO) sheets using a cost-effective and green method. The synthesized Cu(0)-nanoparticle-rGO composites exhibit excellent catalytic activity for the synthesis of symmetrical biaryls from arylboronic acids under microwave irradiation. The reaction proceeds smoothly in base-free conditions with easy recovery and reuse of the catalyst. The methodology is compatible with various functional groups and provides an attractive protocol for the synthesis of symmetrical biaryls with very good yields. HRTEM, XPS and XRD analyses showed the catalyst to be recyclable. The Cu(0) nanoparticles are stable in the rGO nanosheets, and the particle size distribution and oxidation state of the Cu(0) nanoparticle remain the same after performing the chemical reaction.

Synthesis of N, F and S co-doped graphene quantum dots - Kundu, Sumana; Yadav, Ram Manohar; Narayanan, T. N.; Shelke, Manjusha V.; Vajtai, Robert; Ajayan, Pulickel M.; Pillai, Vijayamohanan K. (Nanoscale, 2015)
Graphene quantum dots (GQDs) are a promising category of materials with remarkable size dependent properties like tunable bandgap and photoluminescence along with the possibility of effective chemical functionalization. Doping of GQDs with heteroatoms is an interesting way of regulating their properties. Herein, we report a facile and scalable one-step synthesis of luminescent GQDs, substitutionally co-doped with N, F and S, of similar to 2 nm average size by a microwave treatment of multi-walled carbon nanotubes in a customized ionic liquid medium. The use of an ionic liquid coupled with the use of a microwave technique enables not only an ultrafast process for the synthesis of co-doped GQDs, but also provides excellent photoluminescence quantum yield (70%), perhaps due to the interaction of defect clusters and dopants.

Enhanced electrochemical performance of polypyrrole coated MoS2 nanocomposites as electrode material for supercapacitor application - Thakur, Anukul K.; Choudhary, Ram Bilash; Majumder, Mandira; Gupta, Govind; Shelke, Manjusha V. (Journal of Electroanalytical Chemistry, 2016)
Binary nanocomposites of polypyrrole (PPY) and Molybdenum disulfide (MoS2), with varying weight% of MoS2 viz. MP1, MP2, and MP3 corresponding to 12.5, 25, and 50% of MoS2 respectively, were prepared via. in-situ polymerization method. X-ray diffraction (XRD), field emission scanning microscopy (FESEM), and transmission electron microscopy (TEM) were employed to study the structure and morphology of the prepared nanocomposites. The electrochemical properties were studied by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS) techniques. The nanocomposite electrode material MP2 reached a specific capacitance of 400 F/g at the current density 1 A/g which was higher than that of pure PPY and the other two nanocomposites viz. MP1 and MP3 having different compositions of MoS2 and PPY than that of MP2. It was noteworthy that the maximum capacitance value was obtained only for an optimum dose of MoS2 (MP2 in this case with 25% of MoS2) and any deviation from which ultimately degraded the capacitive performance of the nanocomposite electrode material. This could be attributed to the occurrence of maximum interaction between MoS2 and PPY in the nanocomposite only at a particular concentration of its host materials. The results showed that the specific capacitance of MP2 nanocomposite declined by 7.2% after 5000 cycles. Further, MP2 nanocomposite electrode showed much higher energy density (8.88 Wh/kg) as well as power density (2286 W/kg) which were higher than that shown by PPY electrode. (C) 2016 Elsevier B.V. All rights reserved.

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

Glucose-derived porous carbon-coated silicon nanowires as efficient electrodes for aqueous micro-supercapacitors - Devarapalli, Rami Reddy; Szunerits, Sabine; Coffinier, Yannick; Shelke, Manjusha V.; Boukherroub, Rabah (ACS Applied Materials & Interfaces, 2016)
In this study, we report on carbon coating of vertically aligned silicon nanowire (SiNWs) arrays via a simple hydrothermal process using glucose as carbon precursor. Using this process, a thin carbon layer is uniformly deposited on the SiNWs. Under optimized conditions, the coated SiNWs electrode showed better electrochemical energy storage capacity as well as exceptional stability in aqueous system as compared to uncoated SiNWs. The as-measured capacitance reached 25.64 mF/cm(2) with a good stability up to 25000 charging/discharging cycles in 1 M Na2SO4 aqueous solution.
Keywords: carbon coating; glucose precursor; hydrothermal; microsupercapacitors; silicon nanowires

Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions (vol 5, pg 1251, 2015) - Hussain, Najrul; Gogoi, Pranjal; Azhagan, Muniraj Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R. (Catalysis Science & Technology, 2016)
Correction for ‘Green synthesis of stable Cu(0) nanoparticles onto reduced graphene oxide nanosheets: a reusable catalyst for the synthesis of symmetrical biaryls from arylboronic acids under base-free conditions’ by Najrul Hussain et al., Catal. Sci. Technol., 2015, 5, 1251–1260.

RuO2 center dot nH(2)O nanoparticles anchored on carbon nano-onions: an efficient electrode for solid state flexible electrochemical supercapacitor - Muniraj, Vedi Kuyil Azhagan; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ACS Sustainable Chemistry & Engineering, 2016)
A flexible solid state electrochemical capacitor based on hydrous RuO2 nanoparticles, supported onto the nonporous and highly accessible ion adsorptive carbon nano onions (CNOs), is fabricated in a novel process of modifying a conducting carbon paper to a flexible conducting substrate, separated with a poly(vinyl alcohol)/H2SO4 gel electrolyte. The sol-gel technique tends to form homogeneously dispersed RuO2 nanoparticles with the average size of similar to 2.3 nm on the positive surface curvatures of multilayer fullerene (CNOs), which helps the high diffusivity of ions in both the aqueous and solid state gel electrolytes. The flexible substrate worked excellently as an electrical conductor as well as a stable mechanical support. This solid state flexible energy storage device showed a maximum energy density of 10.62 Whkg(-1) and a maximum power density of 4.456 kWkg(-1) for the hydrous RuO2/CNOs nanocomposite with 94.47% cycling stability even after 4000 cycles.
Keywords: Carbon nano-onions; Electrochemical capacitor; Flexible conducting substrate; Flexible energy storage device; Hydrous ruthenium oxide nanoparticles

Sunlight assisted degradation of dye molecules and reduction of toxic Cr(VI) in aqueous medium using magnetically recoverable Fe3O4/reduced graphene oxide nanocomposite - Boruah, Purna K.; Borthakur, Priyakshree; Darabdhara, Gitashree; Kamaja, Chaitanya Krishna; Karbhal, Indrapal; Shelke, Manjusha V.; Phukan, Pallabi; Saikia, Dulen; Das, Manash R. (RSC Advances, 2016)
In view of the significant impact of magnetically recoverable catalysts in photocatalytic applications, Fe3O4/reduced graphene oxide (rGO) nanocomposite photocatalyst was synthesized by adopting an eco-friendly solution chemistry approach and has been characterized by high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Fe3O4/rGO nanocomposite is efficiently utilized towards photocatalytic degradation of carcinogenic and mutagenic cationic as well as anionic dye molecules namely methyl green (MG), methyl blue (MB) and rhodamine B (RhB) under direct sunlight irradiation. The Fe3O4/rGO nanocomposite also demonstrated excellent photocatalytic reduction of aqueous Cr(VI) solution to nontoxic aqueous Cr(III) solution of more than 96% within 25 min under sunlight irradiation. Moreover, reusability of the magnetically recovered photocatalyst was studied efficiently up to 10 cycles in the degradation process. The catalyst was also characterized after the degradation of the dye molecule and the particle size of the Fe3O4 nanoparticles on the rGO sheets remained unchanged. The present investigation focuses on the importance of the use of Fe3O4/rGO nanocomposite towards photocatalytic degradation of waste water containing organic dye pollutants and toxic Cr(VI), as an easily recoverable and reusable photocatalyst with potential for many environmental remediation applications.

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets

Synthesis of novel Cu2S nanohusks as high performance counter electrode for CdS/CdSe sensitized solar cell - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Dave, Yasha; Debgupta, Joyashish; Shelke, Manjusha V. (Journal of Power Sources, 2016)
An important component of quantum dot sensitized solar cells (QDSSC) is the counter electrode which mediates the regeneration of oxidized quantum dots by reducing the polysulphide electrolyte. However, design and synthesis of an efficient counter electrode material is a challenging task. Herein, we report the synthesis of a unique Cu2S nanohusks directly on FTO coated glass substrates by electrodeposition and used as a counter electrode in QDSSC. When these electrodes are used for the reduction of polysulfide electrolyte in QDSSC, they exhibit higher catalytic activity and photovoltaic performance as compared to the Platinum counter electrode. The power conversion efficiency of about 4.68% has been achieved by optimizing the deposition time of Cu2S. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: counter electrode; Cu2S electrodeposition; Cu2S nanohusks; Quantum dot-sensitized solar cell

Ammonia-modified graphene sheets decorated with magnetic Fe3O4 nanoparticles for the photocatalytic and photo-Fenton degradation of phenolic compounds under sunlight irradiation - Boruah, Purna K.; Sharma, Bhagyasmeeta; Karbhal, Indrapal; Shelke, Manjusha V.; Das, Manash R. (Journal of hazardous materials, 2017)
Synthesis of easily separable and eco-friendly efficient catalyst with both photocatalytic and photo-Fenton degradation properties is of great importance for environment remediation application. Herein, ammonia-modified graphene (AG) sheets decorated with Fe3O4 nanoparticles (AG/Fe3O4) as a magnetically recoverable photocatalyst by a simple in situ solution chemistry approach. First, we have functionalized graphene oxide (GO) sheets by amide functional group and then Fe3O4 nanoparticles (NPs) are doped onto the functionalized GO surface. The AG/Fe3O4 nanocomposite showed efficient photocatalytic activity towards degradation of phenol (92.43%), 2-nitrophenol (2-NP) (98%) and 2-chlorophenol (2-CP) (97.15%) within 70–120 min. Consequently, in case of photo-Fenton degradation phenomenon, 93.56% phenol, 98.76% 2-NP and 98.06% of 2-CP degradation were achieved within 50–80 min using AG/Fe3O4 nanocomposite under sunlight irradiation. The synergistic effect between amide functionalized graphene and Fe3O4 nanoparticles (NPs) enhances the photocatalytic activity by preventing the recombination rate of electron-hole-pair in Fe3O4 NPs. Furthermore, the remarkable reusability of the AG/Fe3O4 nanocomposite was observed up to ten cycles during the photocatalytic degradation of these phenolic compounds.

Co-catalytic metal oxide nanoparticles decorated silicon/hematite core shell nanowire arrays as efficient photo electrodes for water splitting - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ChemistrySelect, 2017)
By looking global energy demands, development of highly efficient stable semiconductor photoelectrodes for photoelectrochemical (PEC) water splitting is highly desirable. Herein, we have fabricated co-catalytic nanoparticles decorated Silicon nanowire (SiNWs)/Hematite(Fe2O3) core sell structures as photo anodes and studied the PEC water oxidation properties. As, Fe2O3 possess weak oxidation kinetics, decoration of NiO and Co3O4 nanoparticles on SiNW/Fe2O3 by hydrothermal method, which acts as co-catalysts to improves the water oxidation reactions. It was found that decoration of Co3O4 nanoparticles enhances the photocurrent up to 2.6 times, whereas for NiO nanoparticles improvement is of 1.5 times when compared to the undecorated electrodes. Along with enhancement of photocurrents, it also shows shift of onset potentials. The effect of the co-catalytic nanoparticles on the enhancement of photocurrent and charge transfer resistance at the interface of electrode-electrolyte have been studied by electrochemical impedance spectroscopy. Further, flat band potentials of the photo electrodes have been measured by using Mott-schottky analysis.
Keywords: Co-catalysts; photo anodes; Photoelectrochemical cell; silicon nanowires; water splitting

Facile synthesis and self-cleaning application of bimetallic (CuSn, CuNi) dendrites - Biswas, Anupam; Kulkarni, Mayuresh A.; Bakthavatsalam, Rangarajan; Mondal, Sourik K.; Dwivedi, Pravin K.; Shelke, Manjusha V.; Devi, Radhamonyamma N.; Banpurkar, Arun G.; Kundu, Janardan (Chemistryselect, 2017)
Bimetallic dendrites (Au, Ag, Pt, Pd) have received intense research interest due to their applications in catalysis and sensing. However, reports on rational synthesis of non-noble bimetallic dendrites that finds self-cleaning applications are scanty. Here, we demonstrate one step co-reduction based galvanic replacement reaction (GRR) for synthesis of alloyed bimetallic dendrites (CuSn, CuNi) with controlled surface roughness and chemical composition. Probing their growth process reveals that i) for CuSn dendrites, co-reduction of Cu2+ and Sn2+ is observed throughout GRR; ii) for CuNi dendrites, Cu nanoparticle, that deposits initially, augments the reduction of Ni2+ which leads to CuNi alloy phase formation during later stages of GRR. These dendrites, naturally having dual degree of surface roughness (micro/nano), have been exploited here for fabricating superhydrophobic surfaces (SHS) with excellent self-cleaning abilities. They show enabling properties such as high contact angle, minimal contact angle hysteresis, and excellent Cassie state stability with no impalement. They maintain superhydrophobicity when exposed to different environmental conditions (low temperature, high temperature, exposure to corroding solutions and UV radiation). The present facile methodology for fabrication of bimetallic dendrites is beneficial for low-cost production of functional nano/micro-materials.

Facile synthesis of 3D anode assembly with Si nanoparticles sealed in highly pure few layer graphene deposited on porous current collector for long life Li‐Ion battery - Shelke, Manjusha V.; Gullapalli, Hemtej; Kalaga, Kaushik; Rodrigues, Marco; Devarapalli, Rami Reddy; Vajtai, Robert; Ajayan, Pulickel M. (Advanced Materials Interfaces, 2017)
With its exceptional theoretical charge capacity, silicon holds great promise as an anode material for realization of high energy density Li-ion batteries. However, extensive volume expansion and poor cycle stability of silicon compromise its actual use. In an effort to tame volume expansion and structural disintegration during cycling, an innovative 3D electrode assembly is fabricated involving continuous layer of graphene coated on porous current collector and Si nanoparticles sealed in as an active material. Graphene deposition and pore formation in metal current collector is achieved in a unique single step synthesis. All the active components like current collector, reacting material, and conducting material are manipulated in a way to produce synergistic architecture in a chemical vapor deposition process. Highly pure graphene deposited in this process enables efficient electron transfer from allover of the surface of silicon nanoparticles and prevents continuous solid electrolyte interphase layer formation. This binder free anode assembly shows extremely stable lithium storage performance for over 1000 cycles with 88% of initial capacity retention and 100% Coulombic efficiency.

Facile synthesis of unique cellulose triacetate based flexible and high performance gel polymer electrolyte for lithium ion batteries - Nirmale, Trupti C.; Karbhal, Indrapal; Kalubarme, Ramchandra S.; Shelke, Manjusha V.; Varma, Anjani J.; Kale, Bharat B. (ACS Applied Materials & Interfaces, 2017)
Lithium ion batteries (LIBs) with polymer based electrolytes have attracted enormous attention due to the possibility of fabricating intrinsically safer and flexible devices. However, economical and eco-friendly sustainable technology is an oncoming challenge to fulfill the ever increasing demand. To circumvent this issue, we have developed a gel polymer electrolyte (GPE) based on renewable polymers like cellulose triacetate and poly (polyethylene glycol methacrylate) p(PEGMA) using a photo polymerization technique. Cellulose triacetate offers good mechanical strength with improved ionic conductivity, owing to its ether and carbonyl functional groups. It is observed that the presence of an open network has a critical impact on lithium ion transport. At room temperature, GPE PC exhibits an optimal ionic conductivity of 1.8 x 10(-3) S cm(-1) and transference number of 0.7. Interestingly, it affords an excellent electrochemical stability window up to 5.0 V vs Li/Li+. GPE PC shows a discharge capacity of 164 mAhg(-1) after the first cycle when evaluated in a Li/GPE/LiFePO4 cell at 0.5 C-rate. Interfacial compatibility of GPE PC with lithium metal improves the overall cycling performance. This system provides a guiding principle toward a future renewable and flexible electrolyte design for flexible LIBs (FLIBs).

One-step synthesis of a MoS2-CuS composite with high electrochemical activity as an effective counter electrode for CdS/CdSe sensitized solar cells - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemelectrochem, 2017)
Inorganic nanostructured composite materials involving metal sulfides are increasingly important in electrochemical applications like solar cells. In this research, we have developed a one-step in situ solvothermal method to synthesize a MoS2-CuS composite. MoS2 sheets increase electron-transfer ability, assisting the improvement in catalytic activity of the MoS2-CuS counter electrode. The charge-transfer resistance derived from impedance spectroscopy for the MoS2-CuS composite counter electrode at the electrode/electrolyte interface is very low, as compared to MoS2, mostly owing to the increased number of active catalytic sites for the reduction of polysulfide electrolyte. The Tafel polarization plot shows excellent electrocatalytic activity of the MoS2-CuS composite towards polysulfide electrolyte. Finally, the CdS/CdSe sensitized solar cell achieves a power conversion efficiency of about 5% upon optimization of the MoS2-CuS composition.

Biomass-mediated synthesis of Cu-doped TiO2 nanoparticles for improved-performance lithium-ion batteries - Kashale, Anil A.; Dwivedi, Pravin K.; Sathe, Bhaskar R.; Shelke, Manjusha V.; Chang, Jia-Yaw; Ghule, Anil V. (ACS Omega, 2018)
Pure TiO2 and Cu-doped TiO2 nanoparticles are synthesized by the biomediated green approach using the Bengal gram bean extract. The extract containing biomolecules acts as capping agent, which helps to control the size of nanoparticles and inhibit the agglomeration of particles. Copper is doped in TiO2 to enhance the electronic conductivity of TiO2 and its electrochemical performance. The Cu-doped TiO2 nanoparticle-based anode shows high specific capacitance, good cycling stability, and rate capability performance for its envisaged application in lithium-ion battery. Among pure TiO2, 3% Cu-doped TiO2, and 7% Cu-doped TiO2 anode, the latter shows the highest capacity of 250 mAh g(-1) (97.6% capacity retention) after 100 cycles and more than 99% of coulombic efficiency at 0.5 A g(-1) current density. The improved electrochemical performance in the 7% Cu-doped TiO2 is attributed to the synergetic effect between copper and titania. The results reveal that Cu-doped TiO2 nanoparticles might be contributing to the enhanced electronic conductivity, providing an efficient pathway for fast electron transfer.

Carbon fabric based solar steam generation for waste water treatment - Higgins, M. W.; Rahmaan, Shakeel A. R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Jha, Neetu (Solar Energy, 2018)
Decontamination of waste water is one of the most practical techniques to tackle the worldwide clean water shortage. In recent times, solar steam based decontamination of contaminated water has been attested as a potential sustainable strategy to get clean water using renewable resources. Herein, we report the utilization of Carbon fabric and Titanium Nanorods on Carbon Fabric for solar steam based water purification techniques. The performance of Carbon Fabric was tested under different conditions and the results proved that Carbon Fabric has excellent light to heat conversion capabilities in both real and ideal conditions. Owing to the excellent performance of Carbon Fabric, it was used for purification of different types of contaminated water. About 99.9% of salt and 87% of organic contaminants were removed from saline water and organic waste water respectively, using a simple low cost carbon fabric based homemade prototype. We also present the application of Titanium Nanorods on carbon fabric for the efficient removal of dye molecules like Rhodamine B from contaminated water using solar driven interfacial steam generation mechanism.
Keywords: Desalination; Dye degradation; Solar steam; Waste water treatment

Electrochemical capacitive energy storage in PolyHIPE derived nitrogen enriched hierarchical porous carbon nanosheets - Deshmukh, Ashvini B.; Nalawade, Archana C.; Karbhal, Indrapal; Qureshi, Mohammed Shadbar; Shelke, Manjusha V. (Carbon, 2018)
Porous and interconnected electrodes based on carbon nanoarchitectures offer comprehensive advantages of large specific surface area and high porosity consequently increasing the specific capacitance of ultracapacitor energy storage systems. Emulsion-templated polymers, PolyHIPEs (Polymerized High Internal Phase Emulsions) are highly porous polymers with a structure of cages interconnected by windows thus provide suitable framework to create such porous carbon nanostructures. Herein, nitrogen enriched porous carbon nanosheets are synthesized by pyrolysis of polymer-silica hybrid PolyHIPE and subsequent silica removal. This nitrogen enriched porous carbon nanosheets when tested as an electrode for ultracapacitor, showed specific capacitance as high as 209 F/g at a current density of 1 A/g in 1 M H2SO4 with excellent capacity retention over long cycling. (c) 2017 Elsevier Ltd. All rights reserved.
Keywords: Energy storage; Nitrogen enriched porous carbon nanosheets; PolyHIPE template; Ultracapacitor

In situ synthesis of nitrogen- and sulfur-enriched hierarchical porous carbon for high-performance supercapacitor - Mehare, Rupali S.; Ranganath, Suresha P.; Chaturvedi, Vikash; Badiger, Manohar. V.; Shelke, Manjusha V. (Energy & Fuels, 2018)
In this work, we present a simple and facile method for the nitrogen (N)- and sulfur (S)- doped porous three-dimensional (3D) spongelike carbon materials via direct pyrolysis of N and S containing polymer N,N'-methylene-bis-acrylamide cross-linked poly(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonic acid) at varying temperatures under inert atmosphere. The obtained nitrogen- and sulfur-doped porous carbons (NSPCs) possess 3D hierarchical porous structure and contain a significantly high amount of N and S species. The concurrent incorporation of N and S successfully modified the surface properties of carbon materials and lead to enhanced capacitive performance. The presented NSPC exhibits specific capacitance of 230 F g(-1) at a current density of 1 A g(-1) and showed excellent cycling stability, depicting a promising material for energy storage devices.

Ni(OH)(2)-Fe2O3/CNOs ternary nanocomposite designed as an anode with complementary properties for high-performance li-ion battery - Dwivedi, Pravin Kumari; Muniraj, Vedi Kuyil Azhagan; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemistryselect, 2018)
Synthesis of the new ternary hybrid composite with excellent electrochemical performances for Li-ion battery is demonstrated. The ternary hybrid composite of Ni(OH)(2)-Fe2O3/Carbon Nano Onions (NFOC) is synthesized by using two-step solution phase method delivers a high reversible discharge capacity of 928 mAhg(-1) at 50 mAg(-1) and 673 mAhg(-1) at a higher current density of 1000 mAg(-1) with excellent rate performance. Additionally, it shows to have stable cycle life up to 1000 cycles with 96% capacity retention and more than 99% of coulombic efficiency. The synergetic effect between Ni(OH)(2), Fe2O3 and carbon nano onions (CNOs) as well as the unique feature of heterostructures are responsible for the improved electrochemical performance of the battery. The reversible reaction of Fe2O3 and Ni(OH)(2) with Li, maintains its long cycle life with higher reversible discharge capacity and CNOs improve the efficient electronic transfer, accommodate substantial volume expansion and maintain the structural integrity of the material during lithiation-delithiation process.
Keywords: Heterostructures; Long cycle stability; Superior rate capability; Ternary Composite; Transition metal oxides

Impedance analysis and equivalent circuit modelling of cells subjected to sinusoidal vibration test using electrochemical impedance spectroscopy - Bangal, Ojas A.; Chaturvedi, Vikash; Babu, P. K. Ajeet; Shelke, Manjusha V. (2019 IEEE Transportation Electrification Conference (ITEC-India), 2019)
Electrochemical impedance spectroscopy is a multipurpose and non-destructive characterization technique in the analysis of electrochemical power sources such as Li-ion cells. The nyquist curve obtained by EIS spectrum of the cell gives information about its overall health. Curve fitting of the EIS nyquist plots further helps in determining the Equivalent Circuit Model (ECM) for a particular cell. In this paper commercial Li-ion cells from three different chemistries; Lithium Nickel Manganese Cobalt Oxide (NMC), Lithium Cobalt Oxide (LCO) and Lithium Iron Phosphate (LFP) are subjected to sinusoidal vibration test as per testing standard mentioned in United States Advanced Battery Consortium (USABC). The EIS measurement of the test cells have been carried out before and after the vibration tests. Curve fitting is carried out on the EIS plots and ECM for the cells is obtained. The components present in ECM and their actual values are estimated from the curve fitting analysis. The magnitude of various resistances like equivalent series resistance (R s ), charge transfer resistance (R ct ) and solid electrolyte interphase resistance (R sei ) is evaluated. This technique is also used in determining the capacitances inside the cell, mainly capacitance (C sei ) due to Solid Electrolyte Interphase layer (SEI) and capacitance due to double layer (C dl ) formation at electrode surface. The resistance in the cell is found to be increased and the capacitances values are decreased after vibration test. Bode plot for the cells are analysed and the overall change in the impedance of cell due to the vibration test is investigated as well. Scanning electron microscopy technique is used on cell electrodes, after vibration test, to validate the actual damage that took place within the cell. The study reveals that the EIS can be used as a non-destructive tool to check cell health after mechanical abuse.

Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors - Chaturvedi, Vikash; Usangonvkar, Saurabh; Shelke, Manjusha V. (RSC Advances, 2019)
The remnants of the anaerobic digestion process, `the digestate,' mainly consist of fibrous lignin and cellulose like molecules, as a significant carbon repository along with some other inorganic impurities. The present work demonstrates the potential use of anaerobically treated fruit and vegetable waste (FVW) as a source of porous carbon for supercapacitor electrode materials. This work suggests that the FVW digestate can inherit silicon (Si) and calcium (Ca) based inorganic impurities, which play an essential role as structure directing agents for digestate derived carbon. These contaminants act as hard templates during carbonization to create hierarchical pores and contribute to an enhancement in surface area. Different batches from an anaerobic biogas digester plant are converted to porous carbon and examined as a potential supercapacitor electrode material. A maximum capacitance of 235 F g(-1) is achieved from DDHPC-4kh carbon with a specific surface area of 2502 m(2) g(-1) at a current density of 1 A g(-1) in an acidic aqueous electrolyte. The results are significant in comparison to other bio-sourced precursors studied previously.

Electrospun nanofibers of Tin phosphide (SnP0.94) nanoparticles encapsulated in a carbon matrix: a tunable conversion-cum-alloying lithium storage anode - Yadav, Poonam; Malik, Wahid; Dwivedi, Pravin Kumari; Jones, Lathe A.; Shelke, Manjusha V. (Energy & Fuels, 2020)
Anodes with improved Li storage capability are required for next-generation lithium batteries. In this work we report a convenient synthesis strategy, based on electrospinning followed by reduction and phosphorization, to prepare a tin phosphide (SnP0.94) phase in a carbon nanofiber matrix. The layered structure offered by the SnP0.94 phase, along with its small size (5-20 nm) encapsulated in the conducting carbon matrix, leads to promising electrochemical Li storage characteristics. This composite has a capacity of 750 mAh g(-1) at 100 mA g(-1) with good cycling and rate stability. Electrochemical studies revealed a faster diffusion coefficient (1.86 x 10(-11) cm(2) s(-1)) for Li in the composite compared to the bare SnP0.94 (8.57 x 10(-14) cm(2) s(-1)), confirming the promise of this class of materials for cation storage in battery anodes.

Highly durable Li-ion battery anode from Fe3O4 nanoparticles embedded in nitrogen-doped porous carbon with improved rate capabilities - Deshmukh, Ashvini B.; Dwivedi, Pravin K.; Nalawade, Archana C.; Qureshi, Mohammed S.; Shelke, Manjusha V. (Journal of Materials Science, 2020)
For next generation, lithium-ion batteries (LIBs) developing high capacity anode materials are crucial with increasing demand of large-scale application. Conversion-type anode materials are promising if stable cycling behavior could be achieved. In this work, a nitrogen-doped porous carbon-Fe3O4(NPC-Fe3O4) nanocomposite is synthesized via a simple and scalable approach. Composite is prepared by pyrolysis of polymer silica hybrid PolyHIPE (high internal phase emulsion) into NPC, and Fe3O4 nanoparticles (NPs) are anchored on its surface via hydrothermal synthesis. As-prepared NPC-Fe3O4 nanocomposite delivers high reversible capacity of around 1001 mAhg(-1)at 0.1 Ag-1 current density and rate capabilities and displays excellent cycling stability as high as 95% capacity retention even after 400 cycles. Superior electrochemical performance of NPC-Fe3O4 is attributed to the hierarchical porous structure and nitrogen doping of carbon which shorten the diffusion path of Li+ and provide ample space to prevent aggregation of Fe3O nanoparticles. [GRAPHICS] .

Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors (vol 9, pg 36343, 2019) - Chaturvedi, Vikash; Usgaonkar, Saurabh; Shelke, Manjusha V. (RSC Advances, 2020)
Correction for `Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors' by Vikash Chaturvedi et al., RSC Adv., 2019, 9, 36343-36350.

High efficiency lithium storage in 3D composite foam of Co3O4 nanoparticles integrated carbon nanohorns - Dwivedi, Pravin K.; Parte, Golu; Thripuranthaka, M.; Shelke, Manjusha V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2021)
A well-designed 3 dimensional (3D) nanocomposite foam of Co3O4 nanoparticles and functionalized carbon nano horns (CNH) is prepared by feasible wet chemistry followed by lyophilization. This 3D nanocomposite foam is evaluated electrochemically as anode material for lithium-ion battery (LIB). 3D hierarchical mesoporous hybrid of functionalized carbon nano horn-Co3O4 (CCO) shows excellent lithium storage properties with long cycle life due to high surface area, good conductivity, 3D interconnected mesoporous structure, mechanical and chemical stability and shortened diffusion path length for Li+ ions during lithiation-delithiation. The Co3O4 nanoparticles incorporated into interconnected CNH foam effectively increases the number of active sites of CCO nanocomposite and consequently increase in the reversible specific capacity and coulombic efficiency. Different compositions of CNH foam with Co3O4 nanoparticles are prepared, among which the CCO 1:1 foam displays reversible capacity of 797 mAhg1 at current density of 0.1 Ag-1 along with excellent rate performance. High specific capacity of around 702 mAhg(-1) is obtained even at the current density of 5 Ag-1.
Keywords: 3D CCO foam; carbon nanohorns; Excellent rate capability; Li ion diffusion coefficient; Long Cycle life

Laser patterning of boron carbon nitride electrodes for flexible micro-supercapacitor with remarkable electrochemical stability/capacity - Karbhal, Indrapal; Basu, Aniruddha; Patrike, Apurva; Shelke, Manjusha V. (Carbon, 2021)
High performance, all solid-state planar micro-supercapacitor (MSC) with interdigitated Boron carbon Nitride (BCN) electrodes are fabricated via fast, scalable laser patterning technique. Heteroatom doping desirably enhances the electrochemical activity of carbon electrodes. This BCN based micro-supercapacitor showed comparatively very high specific capacitance of 72 mFcm(-2) at a current density of 0.15 mAcm(-2). Even at a high current density of 1 mAcm(-2) device showed specific capacitance as high as 17 mFcm(-2). It has demonstrated excellent electrochemical stability when tested up to 80000 cycles without any sign of further decay in capacity/efficiency. This device showed stable capacity even after bending at 150 degrees angle, for 1500 times during cycling showing remarkable flexibility. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: BCN; Co-doping; Energy storage; Flexible; Laser patterning; Micro-supercapacitor

Flexible ultracapacitor device fabricated with an organic electrode material- naphthalene diimide nitrile/reduced graphene oxide - Deshmukh, Ashvini B.; Biradar, Madan R.; Pawar, Meenakshi D.; Bhosale, Sidhanath V.; Shelke, Manjusha V. (Journal of Energy Storage, 2022)
In this work, we have demonstrated a high-performance flexible supercapacitor electrode based on reduced graphene oxide (rGO) and naphthalene diimide nitrile (NDI-CN) composite. The rGO/NDI-CN composite was prepared by a simple approach. This composite was well characterized using various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) etc. Besides, the pi -pi stacking of NDI-CN on rGO surface was confirmed using UV-vis and FTIR techniques. As fabricated rGO/NDI-CN composite was examined as an electrode material for the supercapacitor applications. The rGO/NDI-CN electrode has delivered an excellent specific capacitance (C-sp) of 336 F g(-1) at 0.5 A g(-1)current density. The fabricated supercapacitor (SC) displays robustness with 80 % capacitance retention over 10,000 cycles at higher current density of 10 A g(-1). To further explore the real-world application of electrode materials, the corresponding flexible supercapacitor was designed and examined. The flexible device exhibited an energy density of 9.54 mu Wh cm(-2) at a power density of 0.3 mWcm(-2). These results confirmed that the rGO/NDI-CN electrode material has good potential as an energy storage device. Furthermore, the facile construction and fabrication of flexible device displayed operation of LED when fully charged. The assembled flexible supercapacitor device could be bent and twisted, signifying the potential to be used in practical applications in various high-performance electrochemical devices.
Keywords: flexible supercapacitor; Naphthalene diimide; Organic molecule electrodes; pi -pi interaction; rGO

Atomically dispersed manganese on graphene nanosheets as biocompatible nanozyme for glutathione detection in liver tissue lysate using microfluidic paper-based analytical devices - Baruah, Diksha J.; Thakur, Ashutosh; Roy, Esha; Roy, Kallol; Basak, Sumanjita; Neog, Dipankar; Bora, Himangsu K.; Konwar, Rituraj; Chaturvedi, Vikash; Shelke, Manjusha V.; Das, Manash R. (ACS Applied Materials & Interfaces, 2023)
Recently, single atom catalysts (SACs) featuring M-N-x (M = metal) active sites on carbon support have drawn considerable attention due to their promising enzyme-like catalytic properties. However, typical synthesis methods of SACs often involve energy-intensive carbonization processes. Herein, we report a facile one-pot, low-temperature, wet impregnation method to fully utilize M-N-4 sites of manganese phthalocyanine (MnPc) by decorating molecular MnPc over the sheets of graphene nanoplatelets (GNP). The synthesized MnPc@GNP exhibits remarkable peroxidase-mimic catalytic activity toward the oxidation of chromogenic 3,3 `,5,5(')-tetramethylbenzidine (TMB) substrate owing to the efficient utilization of atomically dispersed Mn and the high surface-to-volume ratio of the porous catalyst. A nanozyme-based colorimetric sensing probe is developed to detect important biomarker glutathione (GSH) within only 5 min in solution phase based on the ability of GSH to effectively inhibit the TMB oxidation. The high sensitivity and selectivity of the developed colorimetric assay enable us to quantitatively determine GSH concentration in different biological fluids. This work, for the first time, reports a rapid MnPc@GNP nanozyme-based colorimetric assay in the solid substrate by fabricating microfluidic paper-based analytical devices (mu PADs). GSH is successfully detected on the fabricated mu PADs coated with only 6.0 mu g of nanozyme containing 1.6 nmol of Mn in the linear range of 0.5-10 mu M with a limit of detection of 1.23 mu M. This work also demonstrates the quantitative detection of GSH in mice liver tissue lysate using mu PADs, which paves the way to develop mu PADs for point-of-care testing.
Keywords: colorimetricsensing; Glutathione; mu PADs; nanozyme; single atom catalyst; tissue lysate

Few-layer graphene lithiophilic and sodiophilic diffusion layer on porous stainless steel as lithium and sodium metal anodes - Patrike, Apurva; Wasnik, Kundan; Shelke, Manjusha V. (Chemistry-An Asian Journal, 2023)
In order to subdue the obvious problem of uneven electric field distribution on regularly used copper/aluminum current collectors for alkali metal batteries, graphene on porous stainless steel (pSS_Gr) was fabricated using the ion etching technique that is employed as an effective host for lithium and sodium metal anodes. The binder-free pSS_Gr demonstrated stable Li plating and stripping at areal current and capacity of 6 mA cm(-2) and 2.54 mAh cm(-2), respectively, for over 1000 cycles with 98% coulombic efficiency (C.E.). Also, in the case of Na metal anode, the host has shown stable performance at 4 mA cm(-2) and 1 mAh cm(-2) over 1000 cycles with similar to 100% C.E.. Further, a full cell composed of Li-plated pSS_Gr as an anode and LiFePO4 as a cathode is electrochemically tested at 50 mA g(-1) current density with stable 100 cycles.
Keywords: Few layer graphene; Free-standing; Li and Na metal functional host; Na depth profiles; post-cycling XPS

Template directed synthesis of boron carbon nitride nanotubes (BCN-NTs) and their evaluation for energy storage properties - Karbhal, Indrapal; Chaturvedi, Vikash; Yadav, Poonam; Patrike, Apurva; Shelke, Manjusha V. (Advanced Materials Interfaces, 2023)
A unique approach has been applied for the synthesis of 1D boron carbon nitride nanotubes (BCN-NTs) using MnO2 nanowires as templates. BCN-NTs have been evaluated in Na-ion batteries, Li-ion batteries, and supercapacitors as electrode material and exhibited excellent and stable electrochemical performance. BCN-NTs as an anode for Na-ion battery has been shown to be highly stable up to 3000 cycles with capacity retention of 95 mAh g(-1), at a high current density of 1 A g(-1). In the case of the Li-ion battery, these BCN-NTs show a specific capacity of 563 mAh g(-1) at a current density of 50 mA g(-1). Finally, when used as an electrode for a supercapacitor, BCN-NTs display a specific capacity of 221 F g(-1) at a current density of 3 A g(-1) and 168 F g(-1) even at a very high current density of 30 A g(-1) exemplifying the excellent rate performance. The multifunctionality and stable performance of BCN-NTs among various electrochemical energy storage systems highlight the robustness of the material and make it an excellent candidate for scalable production and commercialization.
Keywords: 1D-nanostructure; boron carbon nitride nanotubes (BCN-NTs); Co-doping; Li-ion battery; Na-ion battery; Supercapacitors

Ti3C2Tx-Nb2Mo3O14 composite as novel anode to realize high power density combined with high stability in a hybrid lithium-ion capacitor - Pawar, Meenakshi D.; Thripuranthaka, Marulasiddappa; Patrike, Apurva; Deshmukh, Ashvini B.; Chaturvedi, Vikash; Krishnan, Arun; Shivade, Rajkiran; Shelke, Manjusha V. (Energy Technology, 2023)
Lithium-ion capacitors (LICs), with their higher energy density at high power capability, stand out as the future generation of energy-storage devices. Herein, the nanocomposite of Ti3C2Tx MXene with Nb2Mo3O14 is prepared by a one-step hydrothermal method and studied as an electrode material for LIC. The asfabricated composite MXene niobium molybdenum oxide (MXNMO) achieves a high reversible capacity of 205 mAh g(-1) at 100 mA g(-1) current density with outstanding cyclability. Further, asymmetric LIC full-cell device composed of MXNMO anode with supercapacitor grade activated carbon as a cathode delivers an energy density of 37.8 Wh kg(-1) (0.25 A g(-1)) and a higher power density of 4244 W kg(-1) (5 A g(-1)) along with the excellent durability showing 85% capacitance retention over 4000 cycles at 0.5 A g(-1).
Keywords: lithium-ion capacitors; MXene; niobium molybdenum oxides; pseudocapacitive anode materials

Catechol- and phenolic hydroxyl-functionalized partially bio-based (Co) poly(ether sulfone)s with multifarious applicability - Wale, Apparav K.; Jagtap, Ashish S.; Pandey, Priyanshi R.; Dastager, Syed G.; Shelke, Manjusha V.; Ambade, Ashootosh V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2024)
A largely bio-based new bisphenol, namely, 4,4 `-((3,4-dimethoxyphenyl)methylene)-bis(2-methoxyphenol) (DMBM) was synthesized by the reaction of veratraldehyde with guaiacol. DMBM and varying compositions of DMBM and bisphenol A were polycondensed with bis(4-fluorophenyl) sulfone to afford reasonably high molecular weight film-forming (co)poly(ether sulfone)s possessing built-in methoxyl groups. T10 and Tg values of (co)poly(ether sulfone)s were in the range 382-478 degrees C and 171-187 degrees C, respectively indicating their good thermal stability and the values decreased with increase in mol % incorporation of DMBM. The methoxyl groups present in (co)poly (ether sulfone)s were quantitatively de-blocked resulting in the formation of corresponding polymers possessing pendant catechol moieties and free phenolic hydroxyl groups. By virtue of the presence of these functional moieties, (co)poly(ether sulfone)s are amenable for post-polymerization modifications, and exhibited properties such as antimicrobial (23 mm against Staphylococcus aureus and 18 mm against Escherichia coli)), antioxidant (72 % scavenger of free radicals), adhesive (2.24 MPa lap shear strength) and usefulness as redox-active agent in zinc-ion batteries. These data underscore the promise of DMBM as a versatile monomer of wider utility for the synthesis of functional (co)poly(ether sulfone)s capable of expanding their applicability beyond the conventional ones.
Keywords: (Co)poly(ether sulfone)s; adhesive; Antimicrobial; Antioxidant; bio-based; bisphenol; Zinc-ion batteries

Glory of fire retardants in Li-ion batteries: could they be intrinsically safer? - Mishra, Rajat; Anne, Mounika; Das, Sayan; Chavva, Tarunikaa; Shelke, Manjusha V.; Pol, Vilas G. (Advanced Sustainable Systems, 2024)
Lithium-ion batteries (LIBs) have dramatically transformed modern energy storage, powering a wide range of devices from portable electronics to electric vehicles, yet the use of flammable liquid electrolytes raises thermal safety concerns. Researchers have investigated several ways to enhance LIB's fire resistance. Fire retarding molecules functions through cooling effects, scavenging radicals, and forming protective barriers. Incorporating fire-suppressing molecules within the LIBs aims to delay or mitigate thermal runaway scenarios, reducing the risks of fires or explosions. Achieving an optimal balance between safety and performance is a major obstacle in the design of intrinsically safer LIBs. Therefore, it is important to consider their effects on LIB's performance, long-term stability, and environmental impact. To overcome these challenges, collaborative research efforts among academia, industry, and regulatory sectors are necessary. This article reviews state-of-the-art literature associated with LIBs safety or even fire mitigation by introducing solid-state or quasi-solid-state electrolytes as well as modified liquid electrolytes. Moreover, the effectiveness of various strategies in making LIBs intrinsically safer is critically evaluated with an emphasis on fire retardants followed by shedding some light on the remaining challenges.

Hexagonal boron nitride quantum dots embedded on layer-by-layer films for peroxidase-assisted colorimetric detection of β-galactosidase producing pathogens - Majumdar, Sristi; Gogoi, Devipriya; Boruah, Purna K.; Thakur, Ashutosh; Sarmah, Priyakhee; Gogoi, Parishmita; Sarkar, Sanjib; Pachani, Priyakshi; Manna, Prasenjit; Saikia, Ratul; Chaturvedi, Vikash; Shelke, Manjusha V.; et al. (ACS Applied Materials and Interfaces, 2024)
Pathogen detection has become a major research area all over the world for water quality surveillance and microbial risk assessment. Therefore, designing simple and sensitive detection kits plays a key role in envisaging and evaluating the risk of disease outbreaks and providing quality healthcare settings. Herein, we have designed a facile and low-cost colorimetric sensing strategy for the selective and sensitive determination of beta-galactosidase producing pathogens. The hexagonal boron nitride quantum dots (h-BN QDs) were established as a nanozyme that showed prominent peroxidase-like activity, which catalyzes 3,3 `,5,5 `-tetramethylbenzidine (TMB) oxidation by H2O2. The h-BN QDs were embedded on a layer-by-layer assembled agarose biopolymer. The beta-galactosidase enzyme partially degrades beta-1,4 glycosidic bonds of agarose polymer, resulting in accessibility of h-BN QDs on the solid surface. This assay can be conveniently conducted and analyzed by monitoring the blue color formation due to TMB oxidation within 30 min. The nanocomposite was stable for more than 90 days and was showing TMB oxidation after incubating it with Escherichia coli (E. coli). The limit of detection was calculated to be 1.8 x 10(6) and 1.5 x 10(6) CFU/mL for E. coli and Klebsiella pneumonia (K. pneumonia), respectively. Furthermore, this novel sensing approach is an attractive platform that was successfully applied to detect E. coli in spiked water samples and other food products with good accuracy, indicating its practical applicability for the detection of pathogens in real samples.
Keywords: biopolymer; colorimetric; h-BN quantum dots; nanozyme; pathogens; Sensor

Influence of the crystal plane orientation in enhancing the electrochemical performance of a trication-substituted cathode for Li-ion batteries - Shivamurthy, Bogalera Papaiah; Thripuranthaka, Marulasiddappa; Shelke, Manjusha V.; Nayaka, Girish Praveen (Energy and Fuels, 2024)
High-voltage spinel cathodes with low nickel are promising candidates for Li-ion batteries owing to their high energy and power density, thermal stability, and eco-friendliness. However, the high operating voltage (similar to 4.7 V) leads to the decomposition of electrolytes, structural disorder, and deterioration of the cathode-electrolyte interphase (CEI) as well as hinders practical capability. We have synthesized trication-substituted spinel cathode materials with exposed (111) crystal planes and truncated octahedral shapes. These materials have demonstrated high specific discharge capacity and high rate capability up to 1000 cycles with a voltage window of 3.5-5 V. The crystal plane orientation of these materials has been investigated using X-ray diffraction of electrodes and electron microscopic studies and correlated with the electrochemical performance of the surface plane of exposed cathode materials. Among the three synthesized materials, the LMNFA2 cathode has shown a specific discharge capacity of 109.29 mAh g(-1) at 1 C after 1000 cycles with a capacity retention of 76.3%, which is nearly equal to the previously reported dual-phase material with the same metal compositions.

Unveiling a promising active host material for sodium metal anodes through V2AlC max derivation - Wasnik, Kundan; Patrike, Apurva; Shelke, Manjusha V. (ACS Applied Energy Materials, 2024)
To address the issue of nonuniform sodium deposition, in this study, V2ZnC (named VZC), which is synthesized by substituting Zn for Al in V2AlC, is used as a host material to facilitate effective Na utilization. The key concept is to utilize Zn and its forms as an active site to trap Na, while the high mechanical strength of VZC can accommodate volume changes in the sodium metal anode during charging and discharging. VZC displayed regulated plating and stripping at a higher current and capacity of 8 mA cm-2 and 2 mAh cm(-2), respectively, with Coulombic efficiency close to 99.99%.
Keywords: electrodes; Nucleation; overpotential; sodium metal; XPS depth profiling

Enhanced oxygen electrocatalysis in zinc-air batteries via a bifunctional bimetallic organic framework - Shivade, Rajkiran D.; Pandey, Priyanshi; Shelke, Manjusha V. (Journal of Power Sources, 2025)
An efficient bifunctional oxygen electrocatalyst, a nickel-iron metal organic framework (NF-MOF) grown within three-dimensional (3D) nitrogen doped porous carbon (NPC) collectively referred as NF-MOF@NPC, is developed as high performance electrocatalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The synergistic effect of bimetallic active sites coupled with conductive nitrogen doped porous carbon matrix, provides chemical stability, abundant active sites, enhanced electron transfer, and improve catalytic activity. NFMOF@NPC exhibits OER onset potential of 1.60 V at current density of 10 mA cm- 2 with Tafel slope of 126 mV dec- 1 and ORR half wave potential of 0.81 V with electron transfer number of 3.91. A zinc-air battery fabricated using NF-MOF@NPC shows peak power density of 102 mW cm-2 and specific capacity of 741 mAh g-Z 1n. It also exhibits remarkable cycling stability for 120 h at current density of 10 mA cm- 2 highlighting its promise as alternative for conventional platinum on carbon (Pt/C) and ruthenium dioxide (RuO2) electrocatalysts demonstrating its potential for next generation energy storage devices.
Keywords: Bifunctional Electrocatalyst; Rotating disk electrode; zinc-air battery

Enhanced stability of sodium metal anodes in covalent triazine frameworks via progressive nucleation with optimized conducting composite matrix - Wasnik, Kundan; Bhatt, Rajesh C.; Shelke, Manjusha V. (Small, 2025)
Organic materials offer exciting possibilities to improve rechargeable battery performance in multiple ways. This study explores the Covalent Triazine Framework (CTF) as an interlayer to modulate progressive sodium nucleation and subsequent recurrent deposition/extraction in an anode-less sodium battery. The optimized composite, C60R40, which combines CTF with reduced graphene oxide (rGO), has demonstrated its effectiveness as a host. In half cell Na electrodeposition, the C60R40 host exhibits 99.9% coulombic efficiency at an applied current density and areal capacity of 6 mA cm-2 and 2 mAh cm-2, respectively, for 500 cycles. The stable performance is also observed in both full-cell and anode-less battery configurations. When paired with Na3V2(PO4)2F3, the sodium-plated C60R40 demonstrated a stable discharge capacity of 110 mAh g-1. Furthermore, the anode-less sodium battery configuration, with Na3V2(PO4)3 cathode, achieved a promising discharge capacity exceeding 50 mAh g-1 without any additional modifications. These findings highlight the significant role of organic materials in improving the performance of rechargeable sodium metal batteries.
Keywords: anode-less batteries; CTF; instantaneous and progressive nucleation; Nucleation and growth; SEI

In situ solid-state synthesis of nitrogen-enriched porous carbon nanosheets from petroleum coke for lithium-ion hybrid capacitors - Benoy, Santhi Maria; Das, Anoushka K.; Sarmah, Debashis; Pawar, Meenakshi; Shelke, Manjusha V.; Saikia, Binoy K. (Energy & Fuels, 2025)
Lithium-ion capacitors (LICs) have emerged as a next-generation energy storage technology, offering a unique balance between the high energy density of lithium-ion batteries and the fast charge-discharge capability of supercapacitors. However, the development of high-performance anode materials remains a major challenge due to the trade-off between capacity, rate capability, and long-term cycling stability. Herein, we report a novel in situ solid-state synthesis approach for the scalable production of nitrogen-enriched porous carbon nanosheets (mBG1) from petroleum coke, an abundant industrial byproduct. The hierarchical porosity and optimized nitrogen functionalities of mBG1 facilitate rapid lithium-ion diffusion, enhanced electronic conductivity, and robust structural stability. Electrochemical characterization in lithium-ion half-cells demonstrates an exceptional specific capacity of 388 mAh g-1 at 0.1 A g-1, with an outstanding capacity retention of 92.7% over 1000 cycles (261.2 mAh g-1) at 1 A g-1. To validate its practical applicability, a full LIC coin cell was fabricated using mBG1 as the anode and commercial super activated carbon (super AC) as the cathode, achieving a specific capacitance of 44 F g-1 at 1 A g-1, a high energy density of 93.29 Wh kg-1 at 0.5 A g-1, and an impressive power density of 20.34 kW kg-1 at 10 A g-1, with 74% capacitance retention after 5000 cycles. The integration of ultrahigh nitrogen doping, hierarchical porosity, and scalable synthesis techniques offers a new pathway for designing next-generation lithium-ion capacitors with enhanced efficiency, stability, and economic viability. These findings establish mBG1 as a high-performance, scalable, and sustainable anode material for next-generation LICs, offering a transformative pathway for the valorization of petroleum coke in advanced energy storage applications.

Investigations into the nucleation dynamics of the stable Na-metal anode: revealing the role of a tin-infused carbon nanofiber interlayer - Wasnik, Kundan; Yadav, Poonam; Ahuja, Manuj; Mirzapure, Vinay; Johari, Priya; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Fundamental understanding and controlling of sodium nucleation are essential for enhancing the performance, safety, and longevity of sodium metal batteries, which is not yet clearly understood in the case of sodium metal batteries. The present study showcases how a modification in the host material influences nucleation kinetics. Current-time transient studies on copper, carbon nanofiber, and tin-embedded carbon nanofiber interlayers employing the Scharifker-Hills model elucidate the mode of nucleation. This work tries to delve deep and presents a case study on how a tin-based interlayer can not only minimize the barrier for sodium nucleation but also direct the sequential progressive and instantaneous nucleation of sodium metal while reducing the overpotential substantially, resulting in crystalline, uniform Na-metal deposition. Further, to account for the complex dynamics of solid electrolyte interphase (SEI) formation distinctly associated with alkali metal deposition, the SEI-fracture model has been included, and the quantification of electrochemical nucleation parameters is obtained. The results provide important insights into the sodium nucleation mechanism, paving the way to counter dendrite formation and SEI dissolution issues of the Na-metal anode.
Keywords: overpotential; progressiveand instantaneous nucleation; Scharifker-Hills model; SEI-fracture model; tin interlayer

Unlocking enhanced redox dynamics: the power of a bifunctional catalytic zinc phosphide interface in full cell and pouch lithium-sulfur batteries - Das, Anoushka K.; Yadav, Poonam; Verma, Tushar S.; Marulasiddappa, Thripuranthaka; Krishnamurty, Sailaja; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Lithium-sulfur (Li-S) batteries face significant challenges, such as polysulfide dissolution, sluggish reaction kinetics, and lithium anode corrosion, hindering their practical application. Herein, we report a highly effective approach using a zinc phosphide (ZnP2) bifunctional catalyst to address these issues. The ZnP2 catalyst effectively anchors lithium polysulfides (LiPSs), catalytically reactivates them, and enhances lithium-ion diffusion. Utilizing a ZnP2-modified separator in a Li-S half-cell achieves an impressive initial capacity of 1145.4 mAh g-1, retaining 954 mAh g-1 and 99.8% Coulombic efficiency after 100 cycles, compared to the pristine separator. The underlying reaction mechanisms are thoroughly investigated through post-mortem analyses and density functional theory (DFT) calculations. Moreover, a Li-S full cell with an E/S ratio of 10 mu L mg-1 demonstrates stable cycling performance, achieving an initial capacity of 797.5 and 534 mAh g-1 after 100 cycles at 0.1C, with a negative-to-positive mass ratio of 3:1. Additionally, the real-world feasibility of lightweight and flexible Li-S pouch batteries with ZnP2-modified separators is explored, showing a stable performance over 100 cycles at 0.1C with 80% capacity retention. This engineered separator can be integrated with advanced sulfur cathodes to create high-energy-density, stable Li-S batteries for commercial applications.
Keywords: catalytic interlayer; full cell; lithium dendrite; lithium sulfur battery; polysulfide shuttling; pouchcell

Zincke-derived viologen covalent organic framework as a high-performance cathode for aqueous zinc-iodine batteries - Das, Gobinda; Shivade, Rajkiran; Pandey, Priyanshi; Varghese, Sabu; Rajput, Nitul; Matouk, Zineb; Martinez, Jose Ignacio; Straubinger, Rainer; Benyettou, Farah; Gandara, Felipe; Olson, Mark A.; Aouad, Samer; et al. (Small, 2025)
Aqueous zinc-iodine (Zn-I2) batteries are among the most promising energy storage technologies, offering high energy density, low cost, and intrinsic safety. However, their practical deployment is hindered by the polyiodide shuttle effect, leading to rapid capacity fading and poor cycling performance. This work demonstrates the application of a crystalline viologen-based covalent organic framework (TAB-DNP-BP COF), synthesized via a one-pot Zincke reaction, as an efficient iodine host material. The cationic backbone of the TAB-DNP-BP COF effectively confines iodine (I2) species and electrostatically traps polyiodides, suppressing their migration and protecting the zinc anode. Zinc-iodine batteries assembled with an I2-enriched TAB-DNP-BP COF (TAB-DNP-BP COF@I2) cathode deliver a high specific capacity of 337 mAh g-1 at 0.5 C, surpassing the performance of most reported COF-, MOF-, and cage-based systems, while exhibiting excellent cycling stability over 5000 cycles. This work highlights the potential of ionic COFs for stabilizing iodine chemistry and offers a promising strategy toward the development of high-performance, durable aqueous Zn-I2 batteries.
Keywords: iCOF; iodine confinement; viologen; zinc-iodine batteries; Zincke reaction